Integrated Glucocorticoids and Traditional Chinese Medicine in a Squamous Lung Cancer Patient with Dermatologic Toxicities Related to Pembrolizumab: A Case Report - Chen YY; Wu T; Yang G; Yu J (Clinical, Cosmetic and Investigational Dermatology)
Yu Yi Chen,1– 3,* Tongtong Wu,4,* Guowang Yang,4 Jie Yu4 1State Key Laboratory of Traditional Chinese Medicine Syndrome, The second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People’s Republic of China; 2Chinese Medicine Guangdong Laboratory, Hengqin, Guangdong, People’s Republic of China; 3Postdoctoral Research Workstation, Guangdong Provincial Hospital of Traditional Chinese Medicine, Guangzhou, People’s Republic of China; 4Department of Oncology, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guowang Yang, Department of Oncology, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, No. 23, Back Road of Art Gallery, Dongcheng District, Beijing, 100010, People’s Republic of China, Email guowang_yang@163.com Jie Yu, Department of Oncology, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, No. 23, Back Road of Art Gallery, Dongcheng District, Beijing, 100010, People’s Republic of China, Email Jie_Yu2024@163.comAbstract: The report presents the case of a 70-year-old man with advanced squamous lung cancer who developed dermatologic toxicities after receiving Pembrolizumab-based therapy. During the acute phase, the patient was treated with an integrative treatment of glucocorticosteroids and traditional Chinese medicine (TCM) and achieved superior efficacy. The patient presented with blisters and papules distributed covering 60% of the trunk and extremities, along with more than 90% coverage of the hands and feet, graded as a cutaneous immune-related adverse event (irAE) of 3– 4 levels, and accompanied by pruritus, infections, hypercoagulation, hypoproteinemia, and electrolyte disturbance. He was initially on intravenous glucocorticoids synchronized with TCM decoctions for seven days, which effectively intercepted the appearance of fresh cutaneous lesions, with noticeable alleviation of pruritus and other complications. He then began to taper his glucocorticoid dosage with the assistance of TCM. Antihistamines and topicals were used in the first three weeks. As a result, the cutaneous symptoms were well controlled, and he was subsequently transferred for further anti-tumor therapies. In conclusion, integrated glucocorticoids and TCM was used to bring the patient out of the acute phase of high-grade irAE dermatologic toxicity successfully. In this case, the cutaneous symptoms were resolved more rapidly, with earlier glucocorticoid tapering and fewer adverse hormonal effects, without tumor progression.Keywords: immune-related adverse event, irAE, traditional Chinese medicine, TCM, dermatologic toxicity, case report